Phase error reduction of a digitally controlled phase shifter utilizing a variable phase and gain amplifier. (August 2016) - Ozeren, Emre; Çalışkan, Can; Kalyoncu, Ilker; Kayahan, Huseyin; Gurbuz, Yasar
Abstract: This paper presents a variable phase and gain amplifier (VPGA), featured in a 4-bit digitally controlled phase shifter, that enables significant phase error reduction. The functionality of the VPGA is demonstrated by utilizing it between the third and fourth bits of a digitally controlled phase shifter. The first three bits are implemented using distributed active switches based on HBTs and the fourth bit is realized in a final amplification stage based on switching between common-base (CB) and common-emitter (CE) topologies. By the use of the VPGA, RMS phase error is reduced from 22° to 11° with the cost of reduced gain (0.1–2.5 dB) and increased RMS gain error (1.0–2.2 dB). A total of 360° phase shift is achieved in 4 bit resolution with an RMS phase error of 0.1° at 10.5 GHz, and a maximum 11° phase error in 4.5 GHz bandwidth. The chip area is 2.150 mm×1.040 mm including pads, and the VPGA consumes only 0.32 mm×0.410 mm area. The chip is implemented in a 0.25-µm SiGe BiCMOS process. These performance parameters are attributed to the adjustment method by the VPGA applied in this work, which enables superior performance than the-state-of-the-art utilizing similar technologies.